2011
DOI: 10.1029/2011gl048440
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of interannual steric sea level variability

Abstract: Processes contributing to interannual steric sea level variability are studied over the period 1993–2004 using an observationally‐constrained ocean state estimate produced by the ECCO (“Estimating the Circulation and Climate of the Ocean”) consortium. The estimate's dynamical consistency allows for the comprehensive attribution of steric changes in terms of advection, diffusion, and surface buoyancy exchange processes. Steric variations are found to be owing more to oceanic transports than to local surface buo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 21 publications
4
62
0
Order By: Relevance
“…We used the ECCO version 4 ocean reanalysis to unravel the role of ocean transport and surface buoyancy fluxes in the ocean climate fluctuations and analyse the associated signatures on the observed SSH, SST and OC. Our analyses corroborate the findings from past studies on the role of ocean transport and surface buoyancy fluxes in the SSH variations at interannual to decadal timescales (Piecuch and Ponte 2011;Fukumori and Wang 2013;. They also provide new insights on the role of ocean transport and surface buoyancy fluxes in the SST variations and on the relation between the SSH, SST and OC variations at interannual to decadal timescales.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We used the ECCO version 4 ocean reanalysis to unravel the role of ocean transport and surface buoyancy fluxes in the ocean climate fluctuations and analyse the associated signatures on the observed SSH, SST and OC. Our analyses corroborate the findings from past studies on the role of ocean transport and surface buoyancy fluxes in the SSH variations at interannual to decadal timescales (Piecuch and Ponte 2011;Fukumori and Wang 2013;. They also provide new insights on the role of ocean transport and surface buoyancy fluxes in the SST variations and on the relation between the SSH, SST and OC variations at interannual to decadal timescales.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, SST has a different dependency on ocean circulation from SSH: SST depends on the circulation of the upper mixed layer, while SSH depends on the circulation of the ocean from the surface down to the bottom (see, for example, Fig. 1d in Piecuch and Ponte 2011). This will result in different responses of the SST and SSH to the oceanic circulation and variability at interannual and longer timescales that are not correlated.…”
Section: Sst Variations Deduced From the Heat Budget Of The Upper Ocementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the Indian and Pacific Oceans it was shown that DSL change is mainly driven by wind stress, using either a simplified dynamical ocean model (Timmermann et al 2010) or an ocean general circulation model (Nidheesh et al 2013). In addition, Piecuch andPonte (2011, 2012) pointed out that buoyancy forcing is important to explain interannual variability in sea level in both the tropical Atlantic and the tropical Pacific regions. Using AOGCMs, Bouttes et al (2012Bouttes et al ( , 2014 and Bouttes and Gregory (2014) found that changes in sea level can mostly be explained by wind stress (e.g., in the Southern Ocean) but also by heat (e.g., in the North Atlantic) and freshwater fluxes (e.g., in the Arctic Ocean).…”
Section: Discussionmentioning
confidence: 99%
“…Advection, mixing and surface exchanges all affect the steric sea level, and advection contributes to more than half of the low-frequency variability of steric sea level in many regions (Piecuch and Ponte, 2011). We speculate that eddies play a non-negligible role in advection and thus investigating eddies is useful for predicting regional sea-level trends.…”
Section: Motivationmentioning
confidence: 99%